Professional mobility in Islamic societies, 700-1750 (Leiden ; Boston)
xii, 245 sayfa
Keywords: “The present edited volume offers a collection of new concepts and approaches to the study of mobility in pre-modern Islamic societies. It includes nine remarkable case studies from different parts of the Islamic world that examine the professional mobility within the literati and, especially, the social-cum-cultural group of Muslim scholars (“ulamā“) between the eighth and the eighteenth centuries. Based on individual case studies and quantitative mining of biographical dictionaries and other primary sources from Islamic Iberia, North and West Africa, Umayyad Damascus and the Hejaz, Abbasid Baghdad, Ayyubid and Mamluk Syria and Egypt, various parts of the Seljuq Empire, and Hotakid Iran, this edited volume presents professional mobility as a defining characteristic of pre-modern Islamic societies. Contributors Mehmetcan Akpinar, Amal Belkamel, Mehdi Berriah, Nadia Maria El Cheikh, Adday Hernández López, Konrad Hirschler, Mohamad El Merheb, Marta G. Novo, M. A. H. Parsa, M. Syifa A. Widigdo“ --